Pengaruh Beban Kerja, Stres Kerja, dan Kepuasan Kerja Terhadap Quiet Quitting pada Guru di Yayasan X - Farah Syadza Salsabila; Rima Rahmayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of quiet quitting has recently gained increasing attention in human resource management studies as it reflects a decline in work engagement without formal resignation. In the context of foundation-based educational organizations, teachers as professional workers face complex job demands, including academic, administrative, and emotional responsibilities. These conditions may influence teachers’ work behavior, particularly their tendency toward quiet quitting. This study aims to examine the effects of workload, job stress, and job satisfaction on quiet quitting among teachers at Foundation X. This research employed a quantitative approach using a survey method. The population consisted of all teachers at Foundation X, totaling 92 respondents; therefore, a census sampling technique was applied. Data were collected through an online questionnaire using a six-point Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that workload has a positive and significant effect on quiet quitting, job stress has a negative but insignificant effect on quiet quitting, and job satisfaction has a negative and significant effect on quiet quitting. Furthermore, workload, job stress, and job satisfaction simultaneously influence quiet quitting among teachers at Foundation X. These findings suggest that high job demands without adequate job resources may encourage teachers to limit their work engagement as an adaptive response. Therefore, managing workload proportionally and enhancing job satisfaction are crucial strategies to reduce quiet quitting tendencies in foundation-based educational institutions.